A Unique Case of Mantle Cell Lymphoma Masquerading as a Cecal Mass - Sarahi Herrera-Gonzalez; Dema Shamoon; Tingliang Shen; Simon Badin; Yatinder Bains (Case Reports in Gastrointestinal Medicine)
Mantle cell lymphoma (MCL), a type of B-cell non-Hodgkin’s lymphoma, is a rare and aggressive disease with a poor prognosis due to its advanced presentation at diagnosis. It is characterized by a translocation in the Bcl-1 gene, which results in overexpression of cyclin D1. MCL is frequently seen in the form of multiple lymphomatous polyposis (MLP) in which innumerable polyps are observed in the gastrointestinal (GI) tract. In rare instances, MCL presents a single mass. The most common presentation involves male patients in their sixties, with generalized lymphadenopathy, extranodal involvement, and B symptoms (night sweats, fever, and weight loss). Endoscopic findings of MLP include cerebroid folding of the gastric mucosa and innumerable polyps extending from the duodenum to the large intestine and are reported in approximately 9% of all GI lymphomas. Less commonly, only 2–4% of GI malignancies present as a primary GI MCL as a single mass, usually in the stomach and ileocecal region in the intestine. Radiologic findings include lymphadenopathy, splenomegaly, multiple polyposis, or wall thickening with ulceration or mass formation. In most instances, advanced disease is found at diagnosis, for which 5-year survival ranges only from 26 to 46%, even when appropriate treatment is initiated. High mitotic rate, or Ki-67 index, is of prognostic value and is associated with poor prognosis. Treatment involves conventional chemo-immunotherapy consisting of R CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) or RB (rituximab and bendamustine), with the latter being better tolerated and associated with longer progression-free survival. Surgical resection is usually limited to patients in which complications are seen such as bleeding, perforation, or bowel obstruction. We present a unique case of a 70-year-old male with nonbilious, nonbloody emesis, and symptomatic anemia who was found to have a cecal mass consistent with MCL.